Kesaksian Perempuan dalam Al-Qur’an: Studi Analisis Kitab Tafsir Al-Azhar dan Tafsir Al-Mishbah - Mawaddah, Mawaddah; Ulinnuha, Muhammad; Ariyadi, Samsul (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2024)
The discourse on women's testimony in the Qur'an has sparked diverse interpretations among Indonesian exegetes, reflecting various methodological approaches and socio-cultural backgrounds. One of the key verses on this issue is QS. 2:282, which outlines the procedures for recording financial transactions, including the requirement of witnesses. This study compares the interpretations of Hamka in Tafsir al-Azhar and M. Quraish Shihab in Tafsir al-Mishbah. Hamka adheres to a traditionalist stance, arguing that one male witness is equivalent to two female witnesses due to men’s greater involvement in public affairs. Conversely, Quraish Shihab adopts a contextual approach, asserting that testimony should be based on competence rather than gender. Employing qualitative research with content analysis, this study reveals that socio-historical factors significantly shape exegetical conclusions. Hamka’s interpretation reflects the social structure of his time, whereas Quraish Shihab accommodates modern societal changes. This research highlights the evolving nature of Islamic exegesis and emphasizes the importance of contextual reinterpretation in addressing gender justice. By comparing these two prominent tafsir works, the study contributes to the discourse on women's legal standing in Islamic jurisprudence and its implications for contemporary Muslim societies.